Crouching spectres and hidden masters in 'Black Man and White Woman in Dark Green Rowboat' by Russell Banks. Issue 2 (1st October 2017) - Meillon, Bénédicte
Elaborating on Hemingway's iceberg metaphor, which encapsulates the implicit dimension of the short story, this article looks at a minimalist story by Russell Banks, which is haunted by the many subtexts floating under the surface of the text. In this article, I show that both the writing and the reading of this elliptic short story are intrinsically haunted by submerged ghost writings, histories, sister stories and discourses, the tips of which briefly surface here and there in Banks' multi-layered story. A palimpsest haunted by Hemingway's overbearing influence over the modern short story, Russell Banks' 'Black Man and White Woman in Dark Green Row Boat' first limns the shadowy presence of 'Hills Like White Elephants' within its narrative strategy, characterization process, dramatic tension and suggestive descriptive technique. Second, Banks' artful text betrays lingering traces of the history of the United States, perceptible in background Native American vestiges signalling a ghostly presence that has survived dislocation, as well as in the dialogues, gesturing towards the spectral legacy of slavery and Orientalist discourse haunting social relations. Finally, I tackle the embeddedness of the short story into the sequence, exposing how, because of the allographic echoes tying one story to another, the anonymous characters are haunted by their fuller descriptions, names and roles from other stories, whispering their ways into this highly stylized, understated short story, and fleshing out the characters that roam its landscape as mere spectres. I moreover argue that the failure of the American Dream – encapsulated in a metaphor giving the collection its title, Trailerpark – metonymically haunts this narrative and the whole short story cycle. Last but not least, the collection and each story within are furthermore structurally haunted by the ghostly presence of unidentified characters living in one of the trailers, whose blatant obliteration from the diegesis and missing story pose a number of reading problems.